Short X···N Halogen Bonds With Hexamethylenetetraamine as the Acceptor - Anyfanti, Goulielmina; Bauzá, Antonio; Gentiluomo, Lorenzo; Rodrigues, João; Portalone, Gustavo; Frontera, Antonio; Rissanen, Kari; Puttreddy, Rakesh (Frontiers in Chemistry, 2021)
Hexamethylenetetramine (HMTA) and N-haloimides form two kinds of short (CO)2N–X···N and Y–X···N (X, Y = Br, I) halogen bonds. Nucleophilic substitution or ′′ligand-exchange′′ reaction on the peripheral Y of Y–X···N with chloride of N-chlorosuccinimide leads to Cl–X···N halogen-bonded complexes. The X···N distances are significantly shorter when X is covalently bonded to the electron-withdrawing chlorine when compared to bromine or iodine. The 1:1 complex between HMTA and ICl has the shortest Cl–I···N halogen bond [2.272(5) Å] yet reported for an HMTA acceptor. Two halogen bonded organic frameworks are prepared using 1:4 molar ratios of HMTA and N-bromosuccinimide, each has distinct 1D channels, one possessing oval and the second square-grid. The variations in channel shapes are due to tridentate and tetradentate (CO)2N–Br···N coordination modes of HMTA. Density Functional Theory (DFT) studies were performed to gain insights into (CO)2N–X···N interaction strengths (ΔEint). The calculated ΔEint values for (CO)2N–Br···N (–11.2 to –12.5 kcal/mol) are smaller than (CO)2N–I···N (–8.4 to –29.0 kcal/mol). The DFT additivity analysis of (CO2)N–Br···N motifs demonstrates Br···N interaction strength gradually decreases from 1:1 to 1:3 HMTA:N-bromosuccinimide halogen-bonded complexes. An exceptionally similar charge density values ρ(r) for N–I covalent bond and I···N non-covalent bond of a (SO2CO)N–I···N motif signifies covalent character for I···N halogen bonding.